2016
DOI: 10.1007/s00726-016-2237-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of creatine supplementation on thermoregulation and physical (cognitive) performance: a review and future prospects

Abstract: Creatine (Cr) is produced endogenously in the liver or obtained exogenously from foods such as meat and fish.In the human body, 95% of Cr is located in the cytoplasm of skeletal muscle either in a phosphorylated (PCr) or free form (Cr). PCr is essential for the immediate rephosphorylation of adenosine di-phosphate (ADP) to adenosine tri-phosphate (ATP). PCr is rapidly degraded at the onset of maximal exercise at a rate that results in muscle PCr reservoirs being substantially depleted. A well-established strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 138 publications
(178 reference statements)
2
16
0
1
Order By: Relevance
“…Watson and colleagues [117] reported that short-term creatine supplementation (21.6 g/day for 7 days) did not increase the incidence of symptoms or compromise hydration status or thermoregulation in dehydrated (−2%), trained men exercising in the heat. Similar findings were observed by several other groups [118, 119, 127, 128] leading researchers to add creatine to glycerol as a highly effective hyper-hydrating strategy to help athletes better tolerate exercise in the heat [116, 120122, 125, 126]. These findings provide strong evidence that creatine supplementation (with or without glycerol) may serve as an effective nutritional hyper-hydration strategy for athletes engaged in intense exercise in hot and humid environments thereby reducing risk to heat related-illness [5, 129].…”
Section: Other Applications In Sport and Trainingsupporting
confidence: 86%
“…Watson and colleagues [117] reported that short-term creatine supplementation (21.6 g/day for 7 days) did not increase the incidence of symptoms or compromise hydration status or thermoregulation in dehydrated (−2%), trained men exercising in the heat. Similar findings were observed by several other groups [118, 119, 127, 128] leading researchers to add creatine to glycerol as a highly effective hyper-hydrating strategy to help athletes better tolerate exercise in the heat [116, 120122, 125, 126]. These findings provide strong evidence that creatine supplementation (with or without glycerol) may serve as an effective nutritional hyper-hydration strategy for athletes engaged in intense exercise in hot and humid environments thereby reducing risk to heat related-illness [5, 129].…”
Section: Other Applications In Sport and Trainingsupporting
confidence: 86%
“…However, additional creatine supplementation may be indicated for athletes to achieve further improvement in performance. Creatine supplementation (3-4 g/day is shown not only to improve muscle mass and performance, both short term high-intensity and endurance, but also to improve recovery after heavy exercise and avoid muscle soreness and injury (see Roberts et al 2016;Twycross Lewis et al 2016).…”
Section: Creatine In Healthmentioning
confidence: 99%
“…A detailed review of the ergogenic benefits to athletes of creatine elevation in muscle is presented in Twycross Lewis et al (2016). Based initially on studies of Harris et al (1992), supplementation with 20 g per day of creatine monohydrate for 5-10 days was advocated, achieving a 25-30 % increase in muscle TCr, that was then followed by a maintenance dose of 3 g per day.…”
Section: Creatine In Sportmentioning
confidence: 99%
See 1 more Smart Citation
“…Carnosine has a wide spectrum of bioactive properties such as pH buffering, Ca 2+ regulation, anti-glycation and antioxidant activity (9) . Numerous studies in the literature demonstrated the beneficial effects of creatine, carnitine (combined with carbohydrates) or β-alanine (precursor amino-acid of carnosine) supplementation on exercise performance in athletes (10)(11)(12) , and therapeutic potential towards certain disorders in which muscle function is a key component (5,13,14) .…”
mentioning
confidence: 99%